Productivity and efficiency analysis of horticultural co-operatives - Galdeano Gomez, E.
(Es, En)
ilus., 50 ref.
Keywords: ANALISIS ECONOMICO; INDICES ECONOMICOS; PRODUCTIVIDAD; CALIDAD; SECTOR AGRARIO; HORTALIZAS; ESPAÑA